Modeling of Dynamic Responses in Building Insulation - Anna Antonyova; Peter Antony; Endra Joelianto (Journal of Engineering and Technological Sciences, 2015)
In this research a measurement systemwas developedfor monitoring humidity and temperature in the cavity between the wall and the insulating material in the building envelope. This new technology does not disturb the insulating material during testing. The measurement system can also be applied to insulation fixed ten or twenty years earlier and sufficiently reveals the quality of the insulation. A mathematical model is proposed to characterize the dynamic responses in the cavity between the wall and the building insulation as influenced by weather conditions.These dynamic responses are manifested as a delay of both humidity and temperature changes in the cavity when compared with the changes in the ambient surrounding of the building. The process is then modeled through numerical methods and statistical analysis of the experimental data obtained using the new system of measurement.